Estudo do mercado de trabalho em arranjo produtivo local (apl): Território e produção cerâmica em Santa Gertrudes/SP - Fuini, Lucas Labigalini [UNESP] (My University, 2008)
Under the perspective that all productive clusters are related to a respective local labor market, the author analyzes, in this paper, the principal characteristics of labor market associated with Santa Gertrudes/ Sao Paulo region territoriality of manufacturing pavement ceramic. In the context of deep changes in manufacture activity and labor world that drives for new special forms of economic relations, the importance of local labor market notion behind of actual Little and Medium territorialized industries clusters valorization - named APL (Local Productive Arrangements) - are examined in this text, considering it promotes potential of competitiveness and territorial development.
A research of local labor markets in local productive arrangements (APL): Territory and ceramic production in Santa Gertrudes/SP
Keywords: Local labor market; Territory and local productive arrangements